Aplikasi Konsep Tropis dan Luxury Pada Perancangan Restoran Fine Dining - S.P. Honggowidjaja, Hans Vincent Handoko (Intra, 2014)
Fine Dining restaurant is already quite a lot in Indonesia. But in Surabaya, the restaurant quite a bit. This design aims to provide a new destination for Surabaya, both in the culinary field as well as in the design field, by providing an atmosphere that is new and different from the others. In addition, this design also aims to meet the needs of people in Surabaya, who have high appreciation to the food and design.This fine-dining restaurant will be designed in Surabaya, using location near Suramadu bridge, so it has advantages in terms of view atmosphere. With an unique design to support the fine-dining experience that is different from the others, this restaurant will sure catch the heart of food lovers in Surabaya.The design works will be started by literature review as the first step to the basic design, the data on the typology of the existing fine-dining restaurant, and a reference benchmark for ergonomic and acceptable design. Accompanied by technical drawings, mockups of space and perspective, to clarify the design delivered by the designer.